STUDENTS' RESPONSE TOWARD TEACHING ONLINE IN ENGLISH READING CLASS. - steffie mega mahardhika (Universitas 17 Agustus 1945 Semarang, 2021)
Pandemic COVID-19 is not over yet, however as an educator we should be more creative and innovative to motivate our students in teaching and learning processes. One of the important aspects of learning The English language is increasing reading comprehension. It is challenging for the educator to make it happen when doing online teaching and learning processes. To evaluate and analyze the problem the writer makes this research. The purpose of this study is to find out teacher strategies in teaching online reading classes during pandemics. The subjects are the third-semester students of The English Department, Language and Culture Faculty, Universitas 17 Agustus 1945 Semarang. The research was held during the even semester of the academic year 2020/2021. This study uses a descriptive qualitative method. The instruments of the data used in this study are questionnaires filled by the students. The objective of this study is to know some problems that happened during online teaching and learning process in reading class that give an impact in improving their reading comprehension skill. In this research, the writer collected students’ responses and did evaluations to make them more effective and interested in the teaching process. The research indicated that there are some problems faced by the students dealing with learning processes such as teaching strategies, technical problems during online teaching and learning process and they also need extra motivation to improve their reading comprehension. The findings suggested that educators can use diverse teaching strategies in reading class such as scaffolding, QARs (Question and answer relationship), and other strategies to stimulate them being active in online learning processes, the other problem is a technical problem as a signal when they are joining in a class by virtual meeting application. The learners also stated that they need motivation and guidance to use various methods in reading a text. Thus, the process of teaching online doesn’t have a big impact on improving reading comprehension but there are other problems should be noticed.